Exploring the Mechanism of Microarteriogenesis in Porous Silk Fibroin Film. (5th December 2012) - Bai, Lun; Wang, Guangqian; Tan, Xiaoyan; Xu, Jianmei
Abstract : Purpose . Based on the experiment of the microarteriogenesis that is associated with angiogenesis during tissue repair process in porous silk fibroin films (PSFFs), we investigate the characteristics of micro-arteriogenesis and explore its mechanism. Methods . After the porous silk fibroin materials are implanted into the back hypodermal tissue of SD rats, the arteriole development and the morphogenesis of smooth muscle cell are histologically monitored and the micro-arteriogenesis is quantitatively analyzed. Results . 10 days after implantation, the arteriole density reaches the highest level in the junction of silk fibroin materials with tissues. Three weeks later, the arteriolar density in the materials reaches the maximum, and the arterioles in the junction of materials with tissues appear to be in a mature and upgrading state. Modeling of Microarteriogenesis . The arterioles in materials are generated after capillary angiogenesis. It is inferred that arteriolar development does not start until the network of the capillaries is formed. At first, the arterioles grow in the conjunct area of precapillaries with arterioles. Then with the extension of the arterioles, the upgrade of arterioles in connecting area is observed at a later stage. Based on the observation, the conditions and the mechanism of microarterializations as well as the upgrade of arterioles are analyzed.